Komunitas Belajar Sebagai Model Pendidikan Agama pada Institusi Keagamaan Pesantren untuk Meningkatkan Karakter Berbicara Santri - Restu Prana Ilahi; Muhamad Yusuf; Doli Witro (EL-TARBAWI, 2022)
The purpose of this study was to determine the pattern of character education in the learning community at Islamic boarding schools in improving the oral skills of students. The type of research used is descriptive qualitative. The method of data collection and data processing uses literature studies and qualitative analysis, researchers look for data collections from scientific articles in various journals and then analyze them. The results of the study show that learning communities in Indonesia generally use a religious education model to create students' characters who are ready to use, especially in speaking in a pluralistic society, both in terms of language, culture, and religion. Therefore, this learning community is needed to realize a character, religious, and nationalist education. Because with the existence of a learning community, students can find their identity and ability to express themselvesbetter.